A Case Study on Awareness Towards Rpg as Learning and Teaching Aid Tool among Kolej Genius Insan Students - Aiman Zuki Bin Zohan Zuki; Siti Munirah Mohd; Shafinah Kamarudin; Nurhidaya Mohamad Jan; Mohamad Faiz Zainuddin (Kolej Genius Insan, Universiti Sains Islam Malaysia, 2024)
2nd Insan Junior Researchers International Conference 2021 (iJURECON 2021) “STREAM for a Better Life” 15-17th October 2021 Organized By :Kolej GENIUS Insan of Universiti Sains Islam Malaysia